Ungkapan Formulaik dalam Kakawin Baratayuddha (Pupuh 14—15) - Kuntara Wiryamartana (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2007)
A brief survey of cantos 14 and 15 of Kakawin Bharatayuddha reveals the use of formulaic expressions. Those formulaic expressions function not only as fulfilment for metrical reuirements, but also as markers of narrative units, i.e. episodes, sub—episodes and other smaller units. For the readers/audiences they function also as signals pointing the course and the dynamics of the narrative.